Impact of the Environment on Human Migration in Eurasia Proceedings of the NATO Advanced Research Workshop, held in St. Petersburg, 15-18 November 2003 - Scott, E. M.; Alekseev, Andrey Yu.; Zaitseva, Ganna; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2005)
This book is a collection of the articles presented at the NATO Advanced Research Workshop (ARW 979859) held in St. Petersburg, from the 15-18 November 2003 in the Hermitage Museum. The title of the workshop was “The impact of the environment on Human Migration in Eurasia”. More than 40 scientists from Russia, Ukraine, Kazakhstan, Poland, Germany, Switzerland, The Netherlands, United Kingdom, Belgium, Finland, Lithuania and Latvia took part. The themes of the workshop focused on the origin, development, interactions, and migrations of prehistoric and ancient populations, specifically the Scythians, in Eurasia and their relationships with the environment of the time. The discussion of these questions necessitated the participation of specialists from a wide range of academic fields. Beyond any doubt, the environment played an important role in the life of ancient nomadic populations, forming the basis of their economies and influencing various aspects of their mode of life. In this respect, the collaboration of specialists in the Humanities and Science is essential for the solution of scientific questions concerning these peoples. Over the past few years, a large amount of new proxy data related to environmental changes during the Pleistocene and the Holocene and their impact on human life has become available. Our discussion was predominantly limited to environmental changes related to the Holocene. In st this period of about 10000 years, the main focus was on the 1 millennium BC.
Archaeology -- Chronology and Cultural Affinity of the Kurgan Arzhan-2 Complex According to Archaeological Data -- Some Chronological Problems of European Scythia: Archaeology and Radiocarbon -- Migrations of Early Nomads of the Eurasian Steppe in a Context of Climatic Changes -- The North Black Sea Steppes in the Cimmerian Epoch -- Chronology -- Radiocarbon, the Calibration Curve and Scythian Chronology -- The Occupation History of the Southern Eurasis Steppe During the Holocene: Chronology, the Calibration Curve and Methodological Problems of the Scythian Chronology -- 14C Dating of the Siberian Steppe Zone from Bronze Age to Scythian Time -- North-West Caspian Sea Steppe: Environmemt and Migration Crossroads of Pastoral Culture Population During the Third Millennium BC -- Chronology of Pazyryk 2 and Ulandryk 4 Kurgans Based on High Resolution Radiocarbon Dating and Dendrochronology - A Step Towards More Precise Dating of Scythian Burials -- Problems of Construction of a Radiocarbon Chronology for the Time Period 900-300 Cal BC -- Possibilities and Limitations of the Use of Stable Isotopes (?13C and ?15N) from Human Bone Collagen and Carbonate as an Aid in Migration Studies -- OSL Dating in Archaeology -- Environmental study -- The Sun, Climate Change and the Expansion of the Scythian Culture After 850 BC -- Large-Scale Periodicity of Climate Change During the Holocene -- Archaeological and Ethnographic Toxins in Museum Collections -- Changes in Palaeoenvironment and Human Migrations in the Centre of the Russian Plain -- Environmental Changes of the Northeastern Black Sea’s Coastal Region During the Middle and Late Holocene -- Prehistoric Environment, Human Migrations and Origin of Pastoralism in Northern Eurasia -- Environmental Study of the Bronze-Iron Age Transition Period of Eastern Europe -- Applications of Geochemistry to Paleoenvironmental Reconstruction in Southern Siberia -- Pollen and Plant Macroremain Analyses for the Reconstruction of Environmental Changes in the Early Metal Period -- Mid to Late Holocene Climate Change and ITS Influence on Cultural Development in South Central Siberia -- Archaeological Cultures on the Background of Climatic Changes in the Holocene, Poland -- Horse Remains From the Arzhan-1 and Arzhan-2 Scythian Monuments.
Keywords: Earth sciences; Environment; Plant ecology; Anthropology; Earth Sciences, general; Environment, general; Plant Ecology; Anthropology